1998
DOI: 10.1073/pnas.95.9.5133
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of XIST in normal fibroblasts and a somatic cell hybrid: Abnormal localization of XIST RNA in hybrid cells

Abstract: The XIST gene, expressed only from the inactive X chromosome, is a critical component of X inactivation. Although apparently unnecessary for maintenance of inactivation, XIST expression is thought to be sufficient for inactivation of genes in cis even when XIST is located abnormally on another chromosome. This repression appears to involve the association of XIST RNA with the chromosome from which it is expressed. Reactivated genes on the inactive X chromosome, however, maintain expression in several somatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
2
38
2
2
Order By: Relevance
“…The findings indicate that the lack of acetylation coincides with the presence of methylation at promoters of X-inactivated genes. In addition, these results confirm prior reports that human X chromosomes retain the same methylation status in hybrid cells as in intact human cells (29).…”
Section: Methylation Of Promoter Regions Of X-linked Genes Correlatessupporting
confidence: 82%
“…The findings indicate that the lack of acetylation coincides with the presence of methylation at promoters of X-inactivated genes. In addition, these results confirm prior reports that human X chromosomes retain the same methylation status in hybrid cells as in intact human cells (29).…”
Section: Methylation Of Promoter Regions Of X-linked Genes Correlatessupporting
confidence: 82%
“…Previous work has shown that depletion of the "maintenance" DNA methyltransferase Dnmt1 compromises Xist repression (17,36). We verified this in our fibroblasts using siRNA directed against the Dnmt1 transcript.…”
Section: Resultssupporting
confidence: 60%
“…Thus, the absence of Mbd2 increases the probability that Xist gene reactivation will occur. Previous studies reported that artificial demethylation reactivated Xist in about 1% of hypomethylated human fibroblasts (17), while in Dnmt1-deficient differentiated mouse embryonic stem cells, about 15% of cells carried Xist (36). Therefore, deficiency of either DNA methylation or Mbd2 increases the probability of Xist reactivation but does not cause Xist reexpression in every cell.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with reports concerning human-rodent somatic cell hybrids, where the human XIST transcript was not found to be localized correctly to the human X chromosome and where it was suggested that species-specific factors presumably were necessary for cis localization (34,35). Because these studies concerned adult somatic cells rather than ES cells, it may be that murine factors present only during early development and in ES cells are able to ensure the correct cis localization of the human XIST transcript.…”
Section: Discussioncontrasting
confidence: 53%